2014
DOI: 10.1186/2045-3701-4-38
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fatty acid composition and lipid storage by thyroid hormone in mouse liver

Abstract: BackgroundThyroid hormones (THs) are potent hormones modulating liver lipid homeostasis. The perturbation of lipid homeostasis is a hallmark of non-alcoholic fatty liver disease (NAFLD), a very common liver disorder. It was reported that NAFLD patients were associated with higher incidence of hypothyroidism. However, whether abnormal thyroid function contributes to the pathogenesis of NAFLD remains unclear.ResultsWe used in vivo models to investigate the influence of hypothyroidism and TH on hepatic lipid home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…Our results also suggest that fat attenuation provides information that is independent of fat CSA. A recent study demonstrated that hypothyroidism in mice prevents accumulation of fat within the liver but leads to altered hepatic fatty acid composition and glycogen accumulation (27). In our study, patients with AN had normal thyroid-stimulating hormone levels but mildly decreased thyroxine levels.…”
Section: Hormonal Correlates Of Fat Attenuation and Csasupporting
confidence: 55%
“…Our results also suggest that fat attenuation provides information that is independent of fat CSA. A recent study demonstrated that hypothyroidism in mice prevents accumulation of fat within the liver but leads to altered hepatic fatty acid composition and glycogen accumulation (27). In our study, patients with AN had normal thyroid-stimulating hormone levels but mildly decreased thyroxine levels.…”
Section: Hormonal Correlates Of Fat Attenuation and Csasupporting
confidence: 55%
“…Hepatic fatty acids contents were measured as previously described [33, 34]. In brief, about 20 mg liver tissue was homogenized in ice cold PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Liver sections cut in cryostate were stained with Red Oil to reveal triacylglycerol droplets (TAG) [21]. The Sudan Black staining or the Kinyoun's Method were used for detecting lipofucsin granules (oxidative lipids) [22].…”
Section: Lipids Glycogen and Fibrosis Of The Livermentioning
confidence: 99%